Postgender - Salsabila Firdausia Firdausia (STIU Al-Mujtama Pamekasan, 2020)
Postgenderism is a technological way to erode biological, psychological and social roles in gender. Posgenderists assume that gender is an arbitrary boundary that should not need to exist. Posgenderists predict that there will be an accidental elimination of biological and psychological gender through technology, neurotechnology, biotechnology and reproductive technology. This opinion is considered to be detrimental to society and its own individuals, because reproduction will be helped by technology. So that social construction will shift. It is also very incompatible with the word of God and the sunnah of the Prophet. Because it is very explained in the Qur'an that humans were created with only two sexes. This research uses a qualitative method with a descriptive form of analysis that is normative. So analyzing by describing secondary data. Studying about posgenderism actually needs to be done, to anticipate and maintain our nature in accordance with what has been determined by God. Therefore from this research, the writer hopes that it can add a little to the reading knowledge. Keywords: Postgender, Social Role, Human nature